Pengaruh Model Challenge Based Learning Berbasis STEAM Terhadap Keterampilan Proses Sains Siswa SD - Khozinatul Fikriyah, Putri; Suryani, Ela (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of science process skills among elementary school students is caused by teacher-centered learning, which limits students' opportunities to engage directly in scientific activities. This study aimed to determine the differences in students' science process skills before and after the implementation of the Challenge Based Learning model integrated with the Science, Technology, Engineering, Arts, and Mathematics (STEAM) approach, examine its effect on students' science process skills, and identify the improvement in science process skills after learning. This study employed a quantitative approach using a One Group Pretest-Posttest Design. The participants were 32 fourth-grade students of SD Negeri Pringapus 01. Data were collected through pretest-posttest, science process skills questionnaires, student response questionnaires, and observation sheets. Data were analyzed using the paired sample t-test, simple linear regression, and Normalized Gain (N-Gain). The results showed a significant difference in students' science process skills before and after learning. The Challenge Based Learning model integrated with STEAM also had a positive and significant effect on students' science process skills. The average N-Gain score was 0.3155, indicating a moderate improvement. Furthermore, students' science process skills were in the good category, and they showed positive responses toward the learning process. Therefore, the Challenge Based Learning model integrated with the STEAM approach effectively improves elementary school students' science process skills.